1992
DOI: 10.1016/0741-5214(92)90106-i
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced angiogenesis and growth of collaterals by in vivo administration of recombinant basic fibroblast growth factor in a rabbit model of acute lower limb ischemia: Dose-response effect of basic fibroblast growth factor

Abstract: The purpose of this study was to evaluate the effects of exogenous recombinant basic fibroblast growth factor (bFGF) on angiogenesis in severely ischemic tissue beds. We used a two-stage procedure to produce severe ischemia of the hindlimb of 34 New Zealand rabbits. The ischemic hindlimb received intramuscular injection of saline (group A), 1 microgram bFGF (group B), or 3 micrograms bFGF (group C), daily for 2 weeks. Tissue perfusion, skeletal muscle infarction, angiogenesis, and collateral growth were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
146
2
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(154 citation statements)
references
References 45 publications
2
146
2
4
Order By: Relevance
“…24,25 Basic FGF treatment of acute ischemic hindlimbs in rabbit or rat models using arterial ligation enhances angiogenesis, collateral vessel development, and muscle function. 26 The first clinical treatment with the bFGF protein resulted in myocardial revascularization in ischemic myocardium of patients with coronary disease. 9 In this report, we demonstrated by Western blot analysis and ELISA that at least three of the different isoforms of human bFGF (18K, 22.5K and 24-25K) are correctly expressed in different cell lines of various tissue origins after adenovirus-mediated gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Basic FGF treatment of acute ischemic hindlimbs in rabbit or rat models using arterial ligation enhances angiogenesis, collateral vessel development, and muscle function. 26 The first clinical treatment with the bFGF protein resulted in myocardial revascularization in ischemic myocardium of patients with coronary disease. 9 In this report, we demonstrated by Western blot analysis and ELISA that at least three of the different isoforms of human bFGF (18K, 22.5K and 24-25K) are correctly expressed in different cell lines of various tissue origins after adenovirus-mediated gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…FGF-2 stimulates endothelial cell proliferation, migration, and vascular tube formation in three-dimensional cultures in collagen [9] as well as angiogenesis in an in vivo Matrigel pellet assay [10]. The angiogenic efficacy of FGF-2 was confirmed in numerous animal models [11,12]. Although the first phase I clinical trial has shown the safety of intracoronary FGF-2 over a wide range of dosages [3], the optimal dose regimen and delivery strategy for efficacy with respect to cardiac angiogenesis have not been established yet.…”
Section: Commentmentioning
confidence: 99%
“…Gene Therapy (2001) 8, 523-533. dial and limb ischemia. [4][5][6][7][8] In light of these results, clinicians have begun evaluating the therapeutic potential of various angiogenic factors in patients. 9 The recent failure of a clinical trial targeting the ischemic heart, where recombinant VEGF 165 protein was administered by a combination of intercoronary and intravenous injections, 10 has highlighted the need for alternative methods of delivering angiogenic factors in a chronic and sitespecific manner.…”
Section: Introductionmentioning
confidence: 99%